Nano-Sheet-like Morphology of Nitrogen-Doped Graphene-Oxide-Grafted Manganese Oxide and Polypyrrole Composite for Chemical Warfare Agent Simulant Detection - Sanjeeb Lama; Bong-Gyu Bae; Sivalingam Ramesh; Young-Jun Lee; Namjin Kim; Joo-Hyung Kim (Nanomaterials, 2022)
Chemical warfare agents (CWAs) have inflicted monumental damage to human lives from World War I to modern warfare in the form of armed conflict, terrorist attacks, and civil wars. Is it possible to detect the CWAs early and prevent the loss of human lives? To answer this research question, we synthesized hybrid composite materials to sense CWAs using hydrothermal and thermal reduction processes. The synthesized hybrid composite materials were evaluated with quartz crystal microbalance (QCM) and surface acoustic wave (SAW) sensors as detectors. The main findings from this study are: (1) For a low dimethyl methyl phosphonate (DMMP) concentration of 25 ppm, manganese dioxide nitrogen-doped graphene oxide (NGO@MnO2) and NGO@MnO2/Polypyrrole (PPy) showed the sensitivities of 7 and 51 Hz for the QCM sensor and 146 and 98 Hz for the SAW sensor. (2) NGO@MnO2 and NGO@MnO2/PPy showed sensitivities of more than 50-fold in the QCM sensor and 100-fold in the SAW sensor between DMMP and potential interferences. (3) NGO@MnO2 and NGO@MnO2/PPy showed coefficients of determination (R2) of 0.992 and 0.975 for the QCM sensor and 0.979 and 0.989 for the SAW sensor. (4) NGO@MnO2 and NGO@MnO2/PPy showed repeatability of 7.00 ± 0.55 and 47.29 ± 2.69 Hz in the QCM sensor and 656.37 ± 73.96 and 665.83 ± 77.50 Hz in the SAW sensor. Based on these unique findings, we propose NGO@MnO2 and NGO@MnO2/PPy as potential candidate materials that could be used to detect CWAs.